2013
DOI: 10.1371/journal.pone.0067229
|View full text |Cite
|
Sign up to set email alerts
|

PLCE1 Polymorphism and Upper Gastrointestinal Cancer Risk: A Meta-Analysis

Abstract: BackgroundIn recent years, the PLCE1 rs2274223 polymorphism has been extensively investigated as a potential risk factor for upper gastrointestinal cancers, including squamous cell carcinoma (ESCC) and gastric cancer. However, the results of these studies have been inconsistent.MethodsA meta-analysis of 13 case-control studies was performed including more than 11,000 subjects with genotyped PLCE1 rs2274223 polymorphisms. Odds ratios (OR) with 95% confidence intervals (CI) were employed to assess the associatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 32 publications
(36 reference statements)
2
14
0
Order By: Relevance
“…Reduced PLCE1 expression appeared to be more consistent in GC tumors than ESCC tumors, which is partly consistent with the stronger genetic effect of PLCE 1 SNPs in GC, particularly in GCA, as compared with ESCC (6,34). However, the association of PLCE1 SNPs with GNCA was not significant (6,34). The differentially altered PLCE1 expression in UGI cancers warrants further investigation.…”
Section: Discussionsupporting
confidence: 66%
“…Reduced PLCE1 expression appeared to be more consistent in GC tumors than ESCC tumors, which is partly consistent with the stronger genetic effect of PLCE 1 SNPs in GC, particularly in GCA, as compared with ESCC (6,34). However, the association of PLCE1 SNPs with GNCA was not significant (6,34). The differentially altered PLCE1 expression in UGI cancers warrants further investigation.…”
Section: Discussionsupporting
confidence: 66%
“…A number of evidences indicate that PI-PLC ε might favour cancer initiation and/or progression, as in bladder (Cheng et al 2011;Ou et al 2010), murine skin (Bai et al 2004, Oka 2010, Li et al 2009), head and neck cancers (Bourguignon et al 2006). The rs 2274223 polymorphism was significantly associated to increased risk of squamous cell carcinoma and gastric cancer (Hao 2013 By contrast, tumour suppressive role for PI-PLC ε was recently suggested in Ras-triggered cancers (Martins et al 2014). Our present results suggest the existence of a relationship between Ezrin and PI-PLC ε, corroborated by microscopy observations detecting focal and partial cytoplasmic colocalization (Figure 3).…”
Section: Discussionmentioning
confidence: 98%
“…Unfortunately, due to the lack of studies, no comparison for our results can be made in terms of other Caucasian populations. GWAS conducted on gastric and esophageal cancer patients have shown an evident role of rs2274223 gene polymorphism (Abnet et al, 2010;Wang et al, 2010); these findings were confirmed in subsequent replication studies (Palmer et al, 2012) and recent meta-analysis (Hao et al, 2013;Umar et al, 2013). Nevertheless, the ultimate role of this SNP in CRC development needs further investigation in large scale studies.…”
Section: Discussionmentioning
confidence: 75%
“…Rs2274223 of PLCE1 gene was found to have protective effect against CRC development in Chinese population (Li et al, 2012c;Wang et al, 2014), but no significant associations were reported for rs4072037 and rs2294008 variants (Li et al, 2012c;Smith et al, 2012). Recent meta-analysis have confirmed the role of these SNPs for the development of different cancers (Hao et al, 2013;Umar et al, 2013;Zheng et al, 2013), outlining the need of studies on CRC patients.…”
Section: 2mentioning
confidence: 98%